Cyclic fatigue resistance of a blue heat-treated engine-driven file with different angles of canal access using different kinematics; an in vitro study - Eid, Bassem; Kataia, Mohammed; Elsewify, Tarek (Frontiers in Dental Medicine, 2025)
ObjectivesTo evaluate the effect of angle of access and kinematics on the dynamic cyclic fatigue resistance of E3 Azure rotary NiTi files at body temperature.MethodsEighty E3 Azure files, 25/06, were randomly divided into two equal groups according to the kinematics used, rotation, and reciprocation. Each group was further divided into two equal subgroups (n = 20) according to the angle of file access, zero degrees and 30 degrees. The files were placed in custom-made stainless-steel canals and operated using the manufacturer's recommendations for speed, torque, and angle of reciprocation settings till fracture. The time to fracture and the fracture length were measured. Statistical analysis was performed at a significance of 0.05.ResultsSamples instrumented using reciprocation motion had significantly higher time to fracture than those with continuous rotation (p < 0.001). Samples with zero-degree access angle had significantly higher time to fracture than those with 30° (p < 0.001).ConclusionThe motion and the angle of file access significantly influence the cyclic fatigue resistance of E3 Azure files. Reciprocation motion and a smaller angle of access improve the fatigue resistance of E3 Azure files.Clinical relevanceReciprocation motion and establishment of straight-line access enhance the safety and efficiency of E3 Azure files.